Diversity of cyanobacteria at the Alaska North Slope with description of two new genera: Gibliniella and Shackletoniella - Strunecky, Otakar; Raabova, Lenka; Bernardova, Alexandra; Ivanova, Anna Pavlovna; Semanova, Alexandra; Crossley, Joel; Kaftan, David (FEMS microbiology ecology, 2020)
The diversity of cyanobacteria along the Alaskan North Slope was investigated. We isolated and cultivated 57 strains of cyanobacteria and sequenced a section of their rRNA operon containing a fragment of the 16S rRNA gene. Here, we describe 17 found species belonging mainly to families Coleofasciculaceae, Microcoleaceae, Oculatellaceae, Leptolyngbyaceae and to the order Synechococcales. In pursuing a conservative polyphasic approach, we utilized suggested thresholds in 16S rRNA gene differences in parallel with morphological differences between new and already described taxa for the description of new species and genera. Based on a combination of morphological, molecular and ecological analysis of collected and cultured strains we describe two genera Gibliniella and Shackletoniella as well as six cyanobacterial species; Cephalothrix alaskaensis, Tildeniella alaskaensis, Pseudophormidium americanum, Leptodesmis alaskaensis, Albertania alaskaensis and Nodosilinea alaskaensis. Here, a polyphasic approach was used to identify eight novel and nine established cyanobacterial taxa from a previously non-investigated region that uncovered a high degree of biodiversity in extreme polar environments.
Keywords: Sequence Analysis, DNA; Aljaška; sekvenční analýza DNA; Cyanobacteria; Phylogeny; sinice; RNA ribozomální 16S; DNA, Bacterial; RNA, Ribosomal, 16S; DNA bakterií; fylogeneze; Alaska